“Control de nemátodos en Sacha Inchi (Plukenetia Volubilis l.) con el hongo nematófago Pochonia Chlamydosporia en San Sartín – Perú” - Sangama Alegría, Michael Alonso (2016)
The following research work was aimed to determine the best dose and cost of implementing the nematophagous fungus Pochonia chlamydosporia for nematodes control in growing Sacha Inchi. It was developed at agricultural experimental station fields “El Porvenir” – INIA, located in the district of Juan Guerra, from February to September 2013, applying the Completely Randomized Block Design (DBCA), with 5 blocks and 6 treatments. Some Pochonia chlamydosporia fungus concentrations were used multiplied in rice, in doses of 2g, 4g, 8g and 16g per liter of water on each plant, and chemical control (3,6g from plant) and a absolute control. The plant height, leaf area, photosynthesis and nematode population in soil was evaluated. The most important nematodes found according to their population were: Melodoigyne sp, Aphelenchus sp, Tylenchus sp, Rotylenchulus sp, Tylenchorhynchus sp y Helicontylenchus sp. They excelled in control treatments respectively T2, T3 y T4 have shown better control over Meloidogyne sp and Aphelenchus sp. According to plant height, leaf area and chlorophyll content, it excelled treatment T4 and T3 corresponding to 8g and 4g rice multiplied spores of liter of water.